Clinical management of older people with non-small cell lung cancer in England. Issue 9 (6th July 2012) - Beckett, Paul; Callister, Matthew; Tata, Laila J; Harrison, Richard; Peake, Michael D; Stanley, Roz; Woolhouse, Ian; Slade, Mark; Hubbard, Richard B
Abstract : Data for 25261 patients with non-small cell lung cancer whose details were submitted to the National Lung Cancer Audit in England were analysed to assess the effect of age at diagnosis on their clinical management, after accounting for sex, stage, performance status and comorbidity. Multivariate logistic regression showed the odds of having histocytological confirmation and anticancer treatment decreased progressively with age, and was also lower in women. It is likely that these results have a multifactorial explanation, and further research into the attitudes of patients, carers and healthcare professionals, and clinical trials of treatment in older populations, are necessary.